2009
DOI: 10.1111/j.1574-695x.2009.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

The early interferon response of nasal-associated lymphoid tissue toStreptococcus pyogenesinfection

Abstract: Streptococcus pyogenes is a major causative agent of tonsillitis or pharyngitis in children. Streptococcus pyogenes can persist in tonsils, and one-third of children treated with antibiotics continue to shed streptococci and have recurrent infections. Mouse nasal-associated lymphoid tissue (NALT) is functionally analogous to human oropharyngeal lymphoid tissues, and serves as a model for characterization of the mucosal innate immune response to S. pyogenes. Wild-type S. pyogenes induces transcription of both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Immunity was passively transferred to naive mice by CD4 + T cells only when those cells contained IL-17 + T cells. Independence of IFNγ + is consistent with the restrictive effect of IFNγ on Th17 cell differentiation and our observation that IFNγ − / − knockout mice recruit more PMN cells and macrophages into NALT and more effectively clear streptococci from this tissue than WT mice (19). We suggest that IL-17 promotes recruitment of neutrophils and macrophages, which are able to eradicate streptococci from NALT.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Immunity was passively transferred to naive mice by CD4 + T cells only when those cells contained IL-17 + T cells. Independence of IFNγ + is consistent with the restrictive effect of IFNγ on Th17 cell differentiation and our observation that IFNγ − / − knockout mice recruit more PMN cells and macrophages into NALT and more effectively clear streptococci from this tissue than WT mice (19). We suggest that IL-17 promotes recruitment of neutrophils and macrophages, which are able to eradicate streptococci from NALT.…”
Section: Discussionsupporting
confidence: 87%
“…We observed early influxes of neutrophils and macrophages into NALT following i.n. infection of naive mice (19). Thus, amplification of TGF-β1 expression by persistent or multiple infections could be dependent on the influx of polymorphonuclear (PMN) cells and macrophages or on expansion of T cells, which can be a significant source of TGF-β1 (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that IFN-g can prevent local dissemination of GAS bacteria (68) and is indispensable for protection against a lethal skin infection in mice (69). Thus, considering the potential effect of IFN-g on innate cell activation in combination with its IgG3-inducing capabilities, it can be suggested that future vaccines against GAS should aim at inducing Th1 responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, mice infected via oral route, which is the most common natural infection route, are only minimally affected by the pathogen (18). Intranasal infection of mice has been used as a model for studying immunity to and pathogenesis of Group A Streptococcus (19,20). NALT is the mucosa associated lymphoid tissue in the nasal cavity that has functional similarity of Peyer's patch in the gut COX-1 is generally considered a constitutive enzyme and has been implicated in normal cellular homeostasis (22).…”
Section: Discussionmentioning
confidence: 99%